Psychological implications of early marriages: the unhealed wombs and shattered dreams - Shezah Khalid; Abdul Wahab Yousafzai (Khyber Medical University Journal)
Early marriages, defined as unions where one or both partners are under the age of 18, have long been the norm in Pakistan. Despite a legal minimum age of marriage set at 18 for males and 16 for females, this practice persists, often veiled under the guise of tradition, culture, and economic necessity. According to UNICEF, Pakistan ranks among the top countries with the highest rates of child marriages in the world, with approximately 21% of girls marrying before the age of 18. Various research reports have indicated that a significant proportion of young brides in Pakistan may exhibit symptoms of mental illnesses such as post-traumatic stress disorder, anxiety disorder, particularly depression and borderline personality disorder (BPD). There is a pressing need to raise awareness and educate society regarding the potential future risks of this polarizing situation. Additional research is imperative to highlight the urgency of this issue.